Economic Integration Process in Europe and Asia : Comparative Analysis - Skulska, Bogusława (Proces integracji ekonomicznej w Europie i Azji : analiza porównawcza, 2010)
The dynamic development of the regional integration process in the globalised economy has become a fact. The European Union is an example of a formation in which this process is most advanced, and its analysis may give valuable insight into conditions and factors conducive to the intensification of the economic integration. The Asian regionalism is being shaped in extremely diversified considerations, as opposed to the European one. This is connected with the fact that it is faced with the challenge to reconcile high economic, political, and cultural diversification, and it is shaped in the reality of a much strongly globalised economy. Some economic issues discussed on the Asian forum are identical to the European challenges; thus, Asia has the possibility to use the valuable European experience.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 15-24
Keywords: economic integration process; integration in Asia; European integration